2018
DOI: 10.1111/jopr.12988
|View full text |Cite
|
Sign up to set email alerts
|

Preparation Techniques Used to Make Single‐Unit Crowns: Findings from The National Dental Practice‐Based Research Network

Abstract: Purpose: To: (1) determine which preparation techniques clinicians use in routine clinical practice for single-unit crown restorations; (2) test whether certain practice, dentist, and patient characteristics are significantly associated with these techniques. Methods: Dentists in the National Dental Practice-Based Research Network participated in a questionnaire regarding preparation techniques, dental equipment used for single-unit crown preparations, scheduled chair time, occlusal clearance determination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Practitioners’ preferred method for tooth preparation margin design is the chamfer or heavy chamfer finish line [ 17 , 18 ]. It offers optimal marginal bulk for the restorations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners’ preferred method for tooth preparation margin design is the chamfer or heavy chamfer finish line [ 17 , 18 ]. It offers optimal marginal bulk for the restorations.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the mean values obtained by all the participants in the study, the determined 0.5 mm value was best approximated by the t1 participant (0.45 mm), followed by the values of T1, T2, and t2 ( Table 2 ). The values achieved by the t1 participant are less than 0.5 mm for most preparations ( Table 1 and Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 ) contradicting the minimum necessary width for preventing the fracture of posterior zirconia crowns [ 17 , 18 ]. The two experienced participants, T1 and T2, obtained the most stable values ( Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 ) due to their higher experience levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although vertical preparations provide more conservative preparations and biological response to tissues as proven by the literature. A recent study in the US in 2018, showed that most dentists still prefer chamfer/heavy chamfer margin designs, followed by shoulder preparations [40]. This reflects on the lack of sufficient data awareness and education of possible other techniques that can be used by dentist in different situations.…”
Section: Nouh I Et Almentioning
confidence: 99%
“…Adhesion to dentin is more difficulty due to its organic and inorganic composition and high-water content of about 20% [6]. Through the advanced development of composite resin materials, together with the principle of less wear on dental structure [7], there are not many studies in the literature that have focused on the influence of the location of the marginal end and design of the preparation.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%